A Cross Sectional Study On The Perception Of (Im) Politeness Used In Complaint By Indonesian Efl Students - Ratnawinata, Eni (2014)
This research is a cross sectional study that describe the perception of (im) politeness among three groups of level and between gender used in complaint by Indonesian EFL students with their reasons to judge (im) politeness. The aim of this study are to describe the perception of (im) politeness used in complaint among three groups of Indonesian EFL students and based on different gender and to explain the reasons provided by Indonesian EFL students to judge (im) politeness used in complaint.The study uses the descriptive qualitative research and cross sectional study approach in which the research participant were one hundred and fifty Indonesian EFL students in Muhammadiyah University of Surakarta. The data were the perception of (im) politeness used in complaint which represented in form of scale very polite, polite, impolite, very impolite and not sure. The writer employed documentation and questionare form of DCT (Discourse Completion Taks) scenarios in taking the data. The subject of this research were taken using proportional random sampling technique consisting seventy five male and seventy five female participants. They also consist of three group of students which are third semester, fifth semester and seventh semester. The writer analyzed the data by using complaint theory by Trosborg (1995), politeness theory by Brown and Levinson (1987) and impoliteness theory by Culpeper (2010). The research finding shows that there were different perception of (im) politeness used in complaint among three groups of level. SS as group who had higher level of study had better understanding about (im) politeness used in complaint than others groups (TS and FS). Furthermore,most of the participants regarded that indirect complaint as polite while direct complaint considered as impolite. The difference perception of (im) politeness used in complaint also happened between male and female. Female had better perception of (im) politeness on complaint than male because in most of DCT, female have more confidence to judge whether a complaint polite or impolite. While, male prefer to not judge the level of politeness a complaint. The writer found fourteen reasons to judge (im) politeness provided by Indonesian EFL students. They were word choice as 19%, complaint strategies used by complainer as 17,7%, habitual action as 16,4%, distance as 15,3%, intonation as 13,3%, type of sentences as 4,4%, modal as 2,5%, culture as 2,2%, emotion as 1,27%, right as 1,7%, attention getter as 1,2%, punctuation mark as 0,8%, condition or context as 0,2%, and gender as 0,1%. In some cases, there were found some of students who used more than one strategies to judge whether a complaint polite or impolite.